Digital Transformation of Animal Health Data: Proceedings of the AHEAD 2017 Workshop - András Székács (Frontiers Research Topics, 2018)
The Organisation for Economic Co-operation and Development (OECD)'s Co-operative Research Programme on Biological Resource Management for Sustainable Agricultural Systems sponsored the AHEAD 2017 workshop, bringing together experts from the farming and pharmaceutical industries, information and communications technology, policy, research (and more) to create a roadmap to the digital transformation of animal health surveillance. In many countries, policy supports the reduction of antibiotic use and a growing focus in the veterinary practice is to move away from blanket dosage of antibiotics, for example for mastitis. Significant and speedy improvements can take place, but only with coordinated actions supported by the entire value chain. Reducing the use of antibiotics is of massive societal importance, but changing on farm or veterinary methods requires thought and a user-centred approach. The most glaring and addressable challenge is the absence of near real-time data and information. AHEAD 2017 explored how governments globally can benefit from increased digitisation in animal health. For effective monitoring, it is important to first understand the relevant tasks of each stakeholder in the food value chain. In these proceedings we openly discuss and define these tasks, identify existing challenges to completion of these tasks, and suggest the business opportunities overcoming these challenges can create. Through this publication, it is our intention to encourage open discussion, design and co-creation of an improved digital approach to animal health and drug usage in agriculture. The Workshop was sponsored by the OECD Co-operative Research Programme on Biological Resource Management for Sustainable Agricultural Systems, whose financial support made it possible for most of the invited speakers to participate in the Workshop. The opinions expressed and arguments employed in this publication are the sole responsibility of the authors and do not necessarily reflect those of the OECD or of the governments of its Member countries.